Hubungan Dukungan Keluarga Dengan Motivasi Pasien Pasca Stroke Melakukan Fisioterapi Di Rumah Sakit Murni Teguh Sudirman Jakarta - Enggriani, Dwi Rahayu; Sagala, Lam Murni (Indonesian Trust Nursing Journal, 2025)
Stroke is the second most common cause of disability worldwide in individuals over 60 yearsof age and is the top primary diagnosis in long-term care. Physiotherapy helps clients buildstrength and maintain range of motion or ROM and muscle tone in the muscles that havenot been affected by the stroke. Prevention of complications from stroke can be done bycarrying out regular passive or active ROM exercises according to the patient's condition.Family support influences the motivation of stroke sufferers in doing exercise and also hasa big influence in increasing muscle strength. The objective of this study is to find outwhether there is a relationship between family support and the motivation of stroke patientsto undergo physiotherapy at Murni Teguh Sudirman Hospital, Jakarta. The sample in thisresearch was 30 respondents using total sampling technique. The reliability value of familysupport is 0.791 and the reliability value of the motivation questionnaire is 0.746. Data werecollected using a questionnaire prepared using the Guttman scale. And the data analysisused is univariate and bivariate data analysis using chi-square. This research wasconducted in December 2021 – February 2022. The research results obtained an R valueof 0.346 which shows a low correlation and low strength of the relationship between familysupport and motivation. Furthermore, the statistical test results obtained a value of p =0.007. There is a significant relationship between family support and the motivation of strokepatients to undertake physiotherapy. Hospitals should provide planned and continuoustraining for nursing staff by holding special programs to provide guidance and training forfamilies related to physiotherapy training.